Individual autonomy and state involvement in health care. Issue 4 (1st August 2001) - Rice, Thomas
Abstract : This article examines the ethical basis for government involvement in health care. It first provides the case for individual autonomy, focusing on the justifications–particularly ethical ones–for allowing individuals to make their own choices in health care, and to control more of their own resources in doing so. Next, it provides the opposite case–for abridging individual autonomy, and in particular, for redistributing resources from those who are well off to those who are not. The overriding reason for favouring the latter case, which trumps the notion of individual autonomy, is to ensure that individuals who are at a disadvantage have an equal probability of attaining good health.